Pemenuhan Hak Politik Penyandang Disabilitas Mental dalam Pemilihan Umum - Rizkon Maulana; Indriati Amarini; Ika Ariani Kartini (Kosmik Hukum, 2019)
The fulfillment of political rights for persons with mental disabilities in general elections has not been running as it should be. Pros and cons arise when collecting data on citizens who have the right to vote at the time of general elections. This research analyzes how the fulfillment of the political rights of persons with mental disabilities in legislation and the obstacles experienced in fulfilling the political rights of persons with mental disabilities. This research is a normative juridical study using secondary data as the main data, namely books, journals, research results, and legislation. Secondary data were analyzed normatively qualitative. The results showed that the political rights of persons with disabilities, including persons with mental disabilities, are a component of human rights that must be fulfilled in a democratic country. The fulfillment of the political rights of persons with disabilities is generally based on Law Number 8 of 2016, namely Article 13 which stipulates that persons with disabilities have the political right to vote and be elected in public office. These rights are important to be respected, protected and fulfilled in order to achieve justice for eliminating political discrimination against persons with disabilities. As for the obstacles experienced in fulfilling the political rights of persons with mental disabilities, namely the difficulty in conveying socialization materials to persons with mental disabilities and the level of voter participation among persons with mental disabilities is still low.Keywords: Political Rights, General Election, Mental Disability